IMPROVING CHILDREN'S SERI SKILLS THROUGH LOOSE PARTS MEDIA - Rohilah Wati, Nandang Faturohman, Anggi Rahmani (Jurnal Pendidikan dan Penelitian Semesta Mendidik, 2024)
The purpose of this study is to describe the ability of serialization through loose parts media in group B children at PAUD Nurul Ulum Lebak Wangi. The subjects studied were 12 children of group B of PAUD Nurul Ulum Lebak Wangi. The data collection technique uses observation and documentation. The results of this study showed that the average value of the seriation ability in the pre-cycle was 44.79%, in the first cycle the development rate obtained a percentage of 51.04%. and in the second cycle it increased to 93.22%. Based on the description above, it can be concluded that there is an increase in the ability of serialization through loose parts media in group B in Lebak wangi, Serang Regency - Banten.